Effect of exercise intervention on social distance in middle-aged and elderly patients with chronic low back pain - Weng, Lin-Man; Wang, Rui; Yang, Qi-Hao; Chang, Tian-Tian; Wu, Cheng-Cheng; Li, Wen-Long; Du, Shu-Hao; Wang, Yu-Chen; Wang, Xue-Qiang (Frontiers in Aging Neuroscience, 2022)
Background: Increased social distance is one of the manifestations of social impairment. Chronic low back pain (CLBP) is one of factors associated with increased social distance and social withdrawal. Exercise therapy is an effective means to social impairment. However, whether exercise could reduce social distance in patients with CLBP remains unknown. This study aimed to investigate the effect of exercise on social distance in middle-aged and elderly patients with CLBP. Methods: The longitudinal intervention recruited 29 middle-aged and elderly patients with CLBP from various communities in Yangpu District, Shanghai, China. The participants received exercise intervention for 8 weeks. The assessments were conducted before and after the intervention, including social distance, pain intensity, unpleasantness of pain, Roland-Morris Questionnaire (RMDQ), Self-Rating Anxiety Scale (SAS), and Self-Rating Depression Scale (SDS). Intention to treat analysis was performed. Results: After the 8-week exercise intervention, the social distance of patients with CLBP was shorter than that before intervention and showed significant difference (p < 0.05). The scores of pain intensity, unpleasantness of pain, RMDQ, SAS, and SDS also decreased and were significantly different between pre- and post-intervention (p < 0.05). In addition, the social distance, pain intensity, unpleasantness of pain, RMDQ, SAS, and SDS scores of the moderate CLBP group decreased more after the intervention compared with those of the mild CLBP group. Conclusion: The 8-week exercise intervention cannot only shorten the social distance in middle-aged and elderly patients with CLBP but also relieve pain, disability, and negative emotions.